Gaseificação do glicerol a vapor em leito fixo e meio poroso não catalítico e cálculo do balanço energético - Teixeira, Priscila Lane Lemos (2012)
As the gasification process of glycerol acquires an unfavorable energy balance, the operation of a gasifier in heat recovery mode is suggested. In this context, a fixed bed reactor was operated with exhaust gases at a temperature of 820ºC as energy source and continuous electronic injection of glycerol and water. The fixed bed reactor was build with AISI 310 stainless steel and counted with a volumetric capacity of 3,713 liters and alumina with 1,5mm of diameter as the material of the porous bed. The experiments used K type thermocouples, piezoresistive pressure sensors and mass flow control based on a high precision Coriolis sensor. The exhaust gases composition, the energy demand for gasification and the overall efficiency of the process were analyzed in a temperature range from 600 to 800ºC and a glycerol percentage at the mixture ranging from 30 to 90%. To determine the viability of the project, an energy study of the process was performed using the software EES (Engineering Equation Solver). Although the reactor was built using small dimensions, the objective of this work is to obtain qualitative results for the gasification of glycerol with practicality, without risk variables and difficulties involved in large systems. The experiment showed a good conversion of products in hydrogen, presenting a conversion above 50% at a temperature of 750ºC and with a proportion of 70% of glycerol in water and an energy waste of 36MJ/g with gasification efficiency nearby 100%.